A Hands-on to Teach Colour Perception: The Colour Vision Tube - Haagen-Schützenhöfer, Claudia (Scientia in educatione, 2017)
One basic concept for understanding colour phenomena is the concept of vision. Although vision seems to be quite a natural and simple thing, students are often not familiar with the mechanism behind perceiving objects or even “the colour of objects”. This contribution introduces a simple hands-on experiment, the Colour Vision Tube. The Colour Vision Tube facilitates the experience of seeing “coloured” objects illuminated with other than white light sources. These experiences support students in understanding the relevance of the illuminating light and the conception of selective reï¬ection for colour vision.